Childhood actinic keratosis in an albino transforming into squamous cell carcinoma - Shubhangi V Agale; Grace F D'Costa; Bhavana M Bharambe; Varsha Bhatia (Wolters Kluwer Medknow Publications, 2012)
Actinic keratosis is a scaly, cutaneous lesion that is often seen in elderly patients. It is almost never seen in children and young adults. It develops on areas such as the face, ears and dorsa of the hands with chronic sun exposure. Actinic keratosis is a premalignant lesion, since histological changes in the epidermis may progress to squamous cell carcinoma if left untreated. There are roughly 70,000 people with albinism in India. These patients are prone to develop actinic keratosis which may undergo spontaneous remission or develop into invasive squamous cell carcinoma, basal cell carcinoma and malignant melanoma.We present an unusual case of a 35 year old albino who developed actinic keratosis at the age 15 years which progressed to squamous cell carcinoma.